Internet usage among secondary school English teachers / Noor Aza Abd Aziz - Abd Aziz, Noor Aza (2010)
Many issues have been brought up since the introduction of ICT into the school settings. The problems faced by teachers in relation to their Internet usage can be traced to four major barriers namely the lack of training, difficulty in understanding the technical language, difficulty in understanding the English language and lack of computers in school with Internet facilities. Therefore, this study investigated among the English teachers of selected secondary schools in Kuala Terengganu as to how much they know about the Internet, the skills they have, the problems they face and the measures that can be taken to further encourage Internet usage among the English teachers for professional development. This study adopted a survey design that employed both quantitative and qualitative approaches. The instrumentation involved the use of a set of questionnaire and semi-structured interview. The data collected involved a sample of 60 English teachers from nine secondary schools in Kuala Terengganu. Semi-structured interviews were conducted with 5 randomly selected English teachers. The findings of the study revealed that the English teachers surf the Internet mostly at home compared to the school environment and other places. Only 30% incorporated Internet in their teaching and learning. This could be related to the main problem faced which was lack of time. Majority of the teachers learned the Internet informally from friends and colleagues. They perceived the Internet as not difficult and are average skillful in using most of the Internet applications. Majority of respondents have been using the Internet for less than 5 years. As for suggestions to improve, the majority of the teachers suggested for more in-house training. All these findings reveal that the school authorities should look into the problems and try to overcome them So as to encourage more Internet usage among the teachers for professional development.